PENGARUH PENAMBAHAN KAPUR TERHADAP NILAI HASIL UJI KUAT TEKAN BEBAS PADA TANAH LEMPUNG - Cindy Raya Natalia; Mohammad Ikhwan Yani; Fatma Sarie (Universitas Muhammadiyah Banjarmasin, 2022)
ABSTRACT The purpose of this study was to analyze the effect of physical and mechanical properties of the original clay in the Bawan Village area, and to analyze the effect of lime as an additive on the results of the unconfined compressive strength test which had been stabilized with undisturbed soil. The method of soil improvement in this research is to use the method of mixing clay with lime. The results of the physical properties test, according to AASHTO, are grouped into group A-7-6 (6) (clay soil), and according to USCS the soil is classified as CL group. In the unconfined compressive strength test, 0 days and 3 days of curing were carried out, the value of the unconfined compressive strength (qu) of the original clay sample was qu = 0.332 kg/cm2. The highest unconfined compressive strength value was found in 10% lime, which cured for 0 days was qu = 0.455 kg/cm2 and at 3 days curing was qu = 0.645 kg/cm2. And the value of shear strength (cu) against the original clay sample is cu = 0.116 kg/cm2. The highest value of free compressive strength was found in 10% lime, without curing is cu = 0.228 kg/cm2 and at 3 days curing is cu = 0.332 kg/cm2. Based on the research, it was concluded that the more lime and the longer curing time used, the greater the shear strength of the soil.